Clinical medicine : lecture notes - Bradley, John; Gurnell, M.; Wood, Diana (The lecture notes series, 2012)
Clinical Medicine Lecture Notes provides a comprehensive, accessible introduction to the management and treatment of medical conditions. A short manual of techniques on communication and physical examination in Part 1 is supported by the core knowledge required on diseases specific to each body system in Part 2